1983
DOI: 10.4315/0362-028x-46.6.484
|View full text |Cite
|
Sign up to set email alerts
|

Fate of Mycotoxins During Processing of Foodstuffs II - Deoxynivalenol (Vomitoxin) During Making of Egyptian Bread

Abstract: Four batches of Egyptian bread were prepared using flour spiked with deoxynivalenol (DON) at a level of 2 μg/g in one batch and naturally contaminated flour (3.3 μg/g of DON) in the remainder. These breads, as well as the corresponding flour and fermented dough, were analyzed to follow the fate of DON during processing. Gas liquid chromatography (GLC) with electron capture (EC) detection was used for determination of DON and the results from two experiments were confirmed by GLC-mass spectrometric single ion m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…This hypothesis was supported by other studies [39,90]. A 19% reduction in AFB 1 during dough fermentation in bread production was observed [91]. S. cerevisiae B 1 (ng/mL) [67] Aflatoxins -Recent Advances and Future Prospects 82 …”
Section: Decontamination Of Aflatoxins By Yeastssupporting
confidence: 76%
“…This hypothesis was supported by other studies [39,90]. A 19% reduction in AFB 1 during dough fermentation in bread production was observed [91]. S. cerevisiae B 1 (ng/mL) [67] Aflatoxins -Recent Advances and Future Prospects 82 …”
Section: Decontamination Of Aflatoxins By Yeastssupporting
confidence: 76%
“…Bakery processing has been reported to reduce DON contamination in some reports (Abbas, Mirocha, Pawlosky, & Pusch, 1985;Boyacioglu, Hettiarachchy, & D'Appolonia, 1993;Samar et al, 2001;Seitz, Eustace, Mohr, Shogren, & Yamazaki, 1986), while others suggested that DON is highly stable in this process (El-Banna, Lau, & Scott, 1983;Scott, Kanhere, Dexter, Brennan, & Trenholm, 1984;Scott, Kanhere, Lau, & Dexter, 1983;Tanaka, Hasegawa, Yamamoto, Matsuki, & Ueno, 1986), summarized by Kushiro (2008). The results of the present study agree with those of Neira et al (1997), who found the mean and median reduction between dough and final products were 44.3% and 38.0%, with maximum and minimum reduction rates of 96.6% and 16.8%, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…Studies on the effect of decontamination by fermentation used in the processing of food have been mentioned by other authors such as El Banna, Lau, and Scott (1983), Scott (1984) and Bennet and Richard (1996). Results mentioned by Abbas, Mirocha, Pawlosky, and Push (1985) show a recovery of 38-84% of the DON in the production of bread using wheat contaminated by DON.…”
Section: Resultsmentioning
confidence: 97%